Morphological characterization of sulfonated graphene and Nafion composite membrane by dynamic mode atomic force microscopy. (18th August 2015) - Kwon, Osung; Park, Sam; Kim, Joo Gon; Son, Byungrak; Lee, Dong‐Ha
Summary Maintaining proper hydration in the proton exchange membrane (PEM) is a crucial issue for passive air breathing PEM (ABPEM) fuel cells. The inorganic filler Nafion composite membrane has great potential for replacing commercialized PEM for ABPEM. We synthesize sulfonated graphene and Nafion composite membrane by using functionalized graphene to enhance the water content in the membrane. We analyze morphological variation of a sulfonated graphene–Nafion composite membrane by using dynamic mode atomic force microscopy (DMAFM). The phase map and topography of the sulfonated graphene–Nafion composite membrane were simultaneously studied for systematic characterization. Through characterization, we find that the water content on the composite membrane has increased remarkably and that it is related to the morphological variation after the composition. In the composite membrane, the root‐mean‐squared surface roughness has increased compared with pristine Nafion because of the sulfonated graphene. In the DMAFM study, the composite membrane shows an entirely different phase map than the pristine Nafion. The elliptical domains, which have positive phase lags, are created on the composite membrane surface. The creation of these domains reflects the existence of a repulsive interaction between the tip and sample surface because of an increasing adhesive force between the tip and sample. Copyright © 2015 John Wiley & Sons, Ltd.